The Virulence of Escherichia coli O157:H7 Isolates in Mice Depends on Shiga Toxin Type 2a (Stx2a)-Induction and High Levels of Stx2a in Stool - Hauser, Jocelyn R.; Atitkar, Rama R.; Petro, Courtney D.; Lindsey, Rebecca L.; Strockbine, Nancy; O'Brien, Alison D.; Melton-Celsa, Angela R. (Frontiers in Cellular and Infection Microbiology, 2020)
In this study we compared nine Shiga toxin (Stx)-producing Escherichia coli O157:H7 patient isolates for Stx levels, stx-phage insertion site(s), and pathogenicity in a streptomycin (Str)-treated mouse model. The strains encoded stx2a, stx1a and stx2a, or stx2a and stx2c. All of the strains elaborated 105-106 cytotoxic doses 50% (CD50) into the supernatant after growth in vitro as measured on Vero cells, and showed variable levels of increased toxin production after growth with sub-inhibitory levels of ciprofloxacin (Cip). The stx2a+stx2c+ isolates were 90–100% lethal for Str-treated BALB/c mice, though one isolate, JH2013, had a delayed time-to-death. The stx2a+ isolate was avirulent. Both an stx2a and a recA deletion mutant of one of the stx2a+stx2c+ strains, JH2010, exhibited at least a three-log decrease in cytotoxicity in vitro and both were avirulent in the mice. Stool from Str-treated mice infected with the highly virulent isolates were 10- to 100-fold more cytotoxic than feces from mice infected with the clinical isolate, JH2012, that made only Stx2a. Taken together these findings demonstrate that the stx2a-phage from JH2010 induces to higher levels in vivo than does the phage from JH2012. The stx1a+stx2a+ clinical isolates were avirulent and neutralization of Stx1 in stool from mice infected with those strains indicated that the toxin produced in vivo was primarily Stx1a. Treatment of mice infected with Stx1a+Stx2a+ isolates with Cip resulted in an increase in Stx2a production in vivo and lethality in the mice. Our data suggest that high levels of Stx2a in stool are predictive of virulence in mice.